Feasibility studies of strangeness production in heavy-ion interactions at the BM@N experiment using Monte Carlo simulations. (1st August 2022) - Baranov, D; Kapishin, M; Schmidt, H R; Senger, P; Vasendina, V; Zinchenko, A; Zinchenko, D
Abstract: In 2022, the Baryonic Matter at Nuclotron (BM@N) experimental setup at JINR (Dubna) will be ready in its full configuration to investigate heavy-ion interactions. At the same time, the accelerator complex of the Booster and Nuclotron is being prepared to accelerate and deliver extracted heavy-ion beams to the BM@N fixed target zone. One of the physics objectives, which BM@N will be able to pursue, is measurement of the (multi)strange hyperon excitation functions, i.e. hyperon yields at different energies. These measurements can help to determine the equation of state of the high-density baryonic matter. In this paper, the results of the Monte Carlo simulation of the BM@N detector performance for studying strangeness production in heavy-ion interactions in future runs are presented.